2020
DOI: 10.1021/acsabm.0c00815
|View full text |Cite
|
Sign up to set email alerts
|

Highly Permeable Gelatin/Poly(lactic acid) Fibrous Scaffolds with a Three-Dimensional Spatial Structure for Efficient Cell Infiltration, Mineralization and Bone Regeneration

Abstract: Three-dimensional (3D) fibrous scaffolds allowing sufficient cell infiltration are urgently needed for bone tissue engineering. In this study, a highly permeable 3D interconnected scaffold was fabricated by surface bonding of cotton-like nonwoven fibers with micro- and nanoscale architecture using gaseous chloroform. The results of physiochemical characterization indicated that bonding for 90 min with a fiber density of 0.15 g/cm3 could facilitate satisfactory porosity, supportive mechanical properties, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The figure also presents the in vivo implantation for efficient cell ingrowth, and bone repair, courtesy of Wang. [167] crystallinity of 96 and 94% of L-lactide, respectively. Reported data showed that the faster degradation rate of the container was associated with the high crystallinity of the bottle.…”
Section: Compositesmentioning
confidence: 99%
See 4 more Smart Citations
“…The figure also presents the in vivo implantation for efficient cell ingrowth, and bone repair, courtesy of Wang. [167] crystallinity of 96 and 94% of L-lactide, respectively. Reported data showed that the faster degradation rate of the container was associated with the high crystallinity of the bottle.…”
Section: Compositesmentioning
confidence: 99%
“…Thus, PLA has a widespread application in biomedical industry, [31,41,139,152,155,157-159,113-115-120] drug delivery, [73,108,[123][124][125][126][127][131][132][133][134]136,[139][140][141]152,[160][161][162][163] and tissue engineering. [41,115,139,142,145,146,148,160,[163][164][165][166][167] Polymeric drug release occurs in one of three ways: erosion, diffusion, and swelling. It is important to notice that the polymer properties can modify the drug release profile.…”
Section: Biomedicalmentioning
confidence: 99%
See 3 more Smart Citations